FACTORS AFFECTING TAXPAYER COMPLIANCE IN PAYING MOTOR VEHICLE TAXES IN KULON PROGO: FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI KULON PROGO - Yola Arinda Nastiti; Retno Yulianti; Kunti Sunaryo (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2022)
The purpose of this study was to determine the awareness of taxpayers, tax sanctions, the drive thru Samsat system, progresive tax rates, and socialization of taxation on taxpayer compliance in paying motor vehicle taxes. This research was carried out at SAMSAT Kulon Progo, precisely in Kapanewon Sentolo. The number of samples in this study were 110 respondents with the sampling method using convenience sampling. This data collection was done by distributing questionnaires. The data analysis technique used in this research was multiple linear regression analysis. Based on the results of multiple linear regression analysis, it can be seen that taxpayer awareness, tax sanctions, and tax socialization have an effect on taxpayer compliance, while the drive thru system and progressive tax rates have no effect on motor vehicle taxpayer compliance.